Opting for Local Region in SHOX2 Promoter as a DNA Methylation Biomarker for Lung Cancer Diagnosis - Duong, Pham Anh Thuy; Trang, Nguyen Thu; Ngan, Nguyen Thuy; Lan, Vo Thi Thuong (VNU Journal of Science: Natural Sciences and Technology, 2021)
Epigenetic alterations play a main role in the initiation and progression of lung cancer.  CpG methylation in the promoter of the Short Stature Homeobox 2 ( SHOX2 ) gene has been evaluated and validated at different stages of this malignant disease. Several approaches for measuring DNA methylation have been established, including quantitative methylation-specific PCR (qMSP). This is a simple, fast, and cost-effective technique that can be easily applied to clinical practice. In this study, formalin-fixed, paraffin-embedded (FFPE) tissue samples were collected from 30 lung cancer patients and 30 patients suffering from non-cancerous pulmonary diseases.  The methylation level of SHOX2 was evaluated in two CpG-riched regions by using qMSP and one of them could be conferred as a potential biomarker to lung cancer.